Students' Mathematical Problem-Solving Ability Profiles Reviewed from the Level of Confidence in the Circle Material - Triyana, Evi; Gunawan, Gunawan (UM Purwokerto Press, 2025)
This study aims to analyze students' mathematical problem-solving abilities based on their level of self-confidence. The research uses a qualitative descriptive method with data collection through problem-solving tests, confidence questionnaires, and interviews. The results of the questionnaire are grouped into three categories, namely high, moderate, and low. Respondents were taken by purposive sampling technique as many as one student each in the self-confidence category. Data analysis consists of data reduction, presentation of research results, and drawing conclusions. The results of the study show that students with high self-confidence are able to fulfill their problem-solving skills systematically and completely, including proper problem identification, effective strategy planning, accurate solution implementation, and thorough evaluation of results. Students with moderate levels of self-confidence demonstrate varied problem-solving abilities with major weaknesses in the consistency of strategy implementation and evaluation of work results. Students with low self-confidence have difficulty understanding problems and choosing appropriate approaches so they often fail to solve problems properly.